2015
DOI: 10.1007/s00394-015-1011-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of consuming Palmaria palmata-enriched bread on inflammatory markers, antioxidant status, lipid profile and thyroid function in a randomised placebo-controlled intervention trial in healthy adults

Abstract: Evidence from this human study suggests that P. palmata stimulates inflammation, increases serum triglycerides and alters thyroid function; however, these changes are not likely to impact health as changes remained within the normal clinical range. The data from the in vitro study provided indications that IL-8 may contribute to the apparent immunostimulation noted in the human study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 54 publications
0
34
2
Order By: Relevance
“…Contrary to our promising results in DIO-animals, Allsopp et al recently reported that consuming P. palmata -enriched bread stimulated inflammation, and increased serum TG and thyroid stimulating hormone (TSH) in a healthy (non-obese) people [ 50 ]. High level of iodides in P. palmata would stimulate TSH synthesis and secretion from thyroids, leading to enhanced inflammation.…”
Section: Discussioncontrasting
confidence: 98%
“…Contrary to our promising results in DIO-animals, Allsopp et al recently reported that consuming P. palmata -enriched bread stimulated inflammation, and increased serum TG and thyroid stimulating hormone (TSH) in a healthy (non-obese) people [ 50 ]. High level of iodides in P. palmata would stimulate TSH synthesis and secretion from thyroids, leading to enhanced inflammation.…”
Section: Discussioncontrasting
confidence: 98%
“…In contrast to our findings, a recent randomized placebo‐controlled intervention trial conducted in healthy adults showed that P. palmata consumption increased serum TG (Allsopp et al, 2016). In their report, the authors stated that the high temperature of the baking process might result in thermally‐induced transformation and inactivation of the beneficial n −3 fatty acids, and that some of the participants might have failed to provide fasting samples (Allsopp et al, 2016), which might explain this discrepancy, as could the differences in sample size, baseline characteristics, and administration period and dose of P. palmata . One of the limitations of the present study was that it was conducted in Japanese participants; therefore, it is unknown whether our results can be generalized to non‐Japanese populations.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, a Palmaria palmata-enriched bread has been shown to have negative effects in terms of preventing cardiovascular disorders. In a randomized placebo-controlled trial conducted in healthy adults, the bread stimulated inflammation, increasing serum triglycerides and altering thyroid function, although these changes appeared to have negligible influence, since they remained within the normal clinical range [156].…”
Section: Cardiovascular Riskmentioning
confidence: 98%